Low-Code Programming Models: Low-code has the potential to empower more people to automate tasks by creating computer programs. - HIRZEL, MARTIN (Communications of the ACM, 2023)
This article offers clarity of the concept of low-code programming by exploring visual programming languages, programming by demonstration, and programming by natural language. Artificial intelligence, domain-specific languages, and model-view-controller pattern in low-code programming are also discussed.